Photonics and Optoelectronics of 2D Metal‐Halide Perovskites. Issue 31 (27th June 2018) - Qi, Xiang; Zhang, Yupeng; Ou, Qingdong; Ha, Son Tung; Qiu, Cheng‐Wei; Zhang, Han; Cheng, Yi‐Bing; Xiong, Qihua; Bao, Qiaoliang
Abstract: In the growing list of 2D semiconductors as potential successors to silicon in future devices, metal‐halide perovskites have recently joined the family. Unlike other conversional 2D covalent semiconductors such as graphene, transition metal dichalcogenides, black phosphorus, etc., 2D perovskites are ionic materials, affording many distinct properties of their own, including high photoluminescence quantum efficiency, balanced large exciton binding energy and oscillator strength, and long carrier diffusion length. These unique properties make 2D perovskites potential candidates for optoelectronic and photonic devices such as solar cells, light‐emitting diodes, photodetectors, nanolasers, waveguides, modulators, and so on, which represent a relatively new but exciting and rapidly expanding area of research. In this Review, the recent advances in emerging 2D metal‐halide perovskites and their applications in the fields of optoelectronics and photonics are summarized and insights into the future direction of these fields are offered. Abstract : Metal‐halide perovskites exhibit great promise in photonics and optoelectronics applications. Here, a timely review of recent advances in 2D metal‐halide perovskites and their applications in the fields of optoelectronics and photonics for triggering new possibilities in the conceptual development of novel 2D metal‐halide perovskite materials, architectures, and devices is presented.